KC1 effect on the solubility of five different amino acids in water - Ferreira, Luísa (2010)
Using the analytical gravimetric method the solubility of glycine and dl-alanine in aqueous systems of KCl at 323.15 K, and of l-isoleucine, l-threonine and l-serine in the same system, at 298.15 and 323.15 K, were measured for salt concentrations ranging up to 2.0 molal. The solubility data obtained in this work and activity coefficient data collected from literature were used to study the ability of the Pitzer–Simonson–Clegg equations in the thermodynamic description of the ternary systems water–KCl with glycine, dl-alanine or l-serine at different temperatures. The introduction of a temperature dependency on the Wn,Mx and Un,Mx parameters allowed very satisfactory correlation results: the global root mean square deviations (RMSDs) found were 0.0036 for the activity coefficients and 0.87 g of amino acid per kg of water for the solubility data in those ternary systems. The results found for the prediction of dl-alanine solubility in aqueous KCl system at 333.15K showed satisfactory results (RMSD: 0.80 g of dl-alanine per kg of water), but highly dependent on the chosen temperature dependency for the model parameters, suggesting care when extending solubility calculations to temperatures outside the temperature range used in the correlation.